COST OF DEBT: THE IMPACT OF FINANCIAL FACTORS AND NON-FINANCIAL FACTORS - Dirman, Angela (Dinasti Publisher, 2020)
The research objective to be achieved is to provide understanding and knowledge to the public, especially investors and creditors regarding the implications of corporate financial and non-financial factors on cost of debt and can be used as a reference for further researchers as well as a reference for stakeholders (investors, creditors and government) in taking relevant and reliable decisions. The method used is quantitative research with secondary data taken from the financial statements of issuers at IDX with data collection techniques using purposive sampling method. The data analysis used is multiple linear regression. The population in this study were manufacturing companies in the basic industry and chemical sectors listed on the Indonesia Stock Exchange which were carried out for 3 years of observation, namely 2016-2018. The sample was determined by purposive sampling method in order to obtain as many as 60 samples. The analysis technique used is the t statistical test and the classical assumption test which includes the normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. The results of this study indicate that the leverage variable has a positive effect on cost of debt; the variables of profitability, liquidity, managerial ownership, institutional ownership, and independent commissioners did not affect the cos of debt.